Review on Various Data Mining Approaches on Smart Phone (International Journal of Engineering and Computer Science, 2017)
Smartphones are common and becoming more and heightened, with ever-growing computing, marketing, and feeling powers. It has been adjusting the landscape of people's everyday life and has subjected the options for several interesting data mining purposes, which range from wellness and health checking, particular biometric trademark, downtown computing, assistive design, and elder-care, to interior localization and navigation, etc. Individual task popularity is just a core making end behind these applications.